EGR3 Inhibits Tumor Progression by Inducing Schwann Cell‐Like Differentiation - Cai‐hong Chen; Yang Chen; Yi‐nan Li; Heng Zhang; Xiu Huang; Ying‐ying Li; Zhi‐yang Li; Jing‐xia Han; Xin‐ying Wu; Hui‐juan Liu; Tao Sun (Advanced Science)
Abstract The mechanism and function of the expression of Schwann characteristics by nevus cells in the mature zone of the dermis are unknown. Early growth response 3 (EGR3) induces Schwann cell‐like differentiation of melanoma cells by simulating the process of nevus maturation, which leads to a strong phenotypic transformation of the cells, including the formation of long protrusions and a decrease in cell motility, proliferation, and melanin production. Meanwhile, EGR3 regulates the levels of myelin protein zero (MPZ) and collagen type I alpha 1 chain (COL1A1) through SRY‐box transcription factor 10 (SOX10)‐dependent and independent mechanisms, by binding to non‐strictly conserved motifs, respectively. Schwann cell‐like differentiation demonstrates significant benefits in both in vivo and clinical studies. Finally, a CD86‐P2A‐EGR3 recombinant mRNA vaccine is developed which leads to tumor control through forced cell differentiation and enhanced immune infiltration. Together, these data support further development of the recombinant mRNA as a treatment for cancer.